Perovskite Oxide–Based Materials for Photocatalytic and Photoelectrocatalytic Treatment of Water - Nkwachukwu, Oluchi V.; Arotiba, Omotayo A. (Frontiers in Chemistry, 2021)
Meeting the global challenge of water availability neceessitates diversification from traditional water treatment methods to other complementary methods such as photocatalysis (PC) and photoelectrocatalysis (PEC) for a more robust solution. Materials play very important roles in the development of these newer methods. Thus, the quest and applications of a myriad of materials are ongoing areas of water research. Perovskite and perovskite related materials, which have been largely explored in the energy sectors, are potential materials in water treatment technologies. In this review, attention is paid to the recent progress in the application of perovskite materials in photocatalytic and photoelectrocatalytic degradation of organic pollutants in water. Water treatment applications of lanthanum, ferrite, titanate, tantalum (and others) based perovskites are discussed. The chemical nature and different synthetic routes of perovskites or perovskites composites are presented as fundamental to applications.